The Effectiveness of Learning Activities Based on Revised Bloom Taxonomy on Problem-Solving Ability - Dwi Wiranata; I Wayan Widiana; Gede Wira Bayu (Indonesian Journal of Educational Research and Review)
The low problem-solving ability of students was due to the lack of student learning activities, so that learning activities were needed that can motivate students to learn and develop problem-solving skills. This study aimed to analyze the effectiveness of learning activities based on Revised Bloom's Taxonomy on problem-solving abilities. The type of research used was development research with a 4D model. The subjects of this study were four experts and 55 fourth-grade elementary school students. The object of this research was the effectiveness of Revised Bloom's Taxonomy-oriented learning activities. The data collection method used was the non-test method and the test method. The instruments used were questionnaires and description tests. The data analysis technique used was descriptive quantitative statistical data analysis techniques in the form of prerequisite tests and t-tests. The results of this study indicate that the average score of the experimental class was 83.50, while the control class was 74.83, and the t-test results obtained a significance value of 0.969 with an at-count of 0.00 < t-table of 0.05. This research concluded that learning activities based on Revised Bloom's Taxonomy effectively improve students' problem-solving abilities. The implication of this development research was to produce products in the form of learning activities based on Revised Bloom's Taxonomy that can train curiosity, self-confidence and improve students' problem-solving abilities.